Viva la historieta : Mexican Comics, NAFTA, and the Politics of Globalization. - Campbell, Bruce (UPCC book collections on Project MUSE., 2009)
¡Viva la historieta! critically examines the participation of Mexican comic books in the continuing debate over the character and consequences of globalization in Mexico. The focus of the book is on graphic narratives produced by and for Mexicans in the period following the 1994 implementation of the North American Free Trade Agreement (NAFTA), an economic accord that institutionalized the free-market vision of relationships among the United States, Mexico, and Canada. Eight chapters cover a broad range of contemporary Mexican comics, including works of propaganda, romance and adventure, graphic novels, a corporate "brand" series, didactic single-issue books, and a superhero parody series.